A smart approach to aquatic ecosystem protection: IoT-Based Water Quality Monitoring System (WQMAS) - Nik Mohd Kamal, Nik Nor Muhammad Saifudin; Amir Hussin, Amir 'Aatieff; Zainuddin, Ahmad Anwar; Mohd Razali, Muhammad Irfan Zaki; Mohammad Noor, Normawaty; Mohd Razali, Roziawati; Ayub, Mohd Nor Azman; Harman, Muhd Farouk (Penteract Technology, 2025)
In an era increasingly threatened by pollution and climate change, water quality is under serious risk. Spatial water quality monitoring and traditional laboratory testing are inadequate to protect aquatic ecosystems. An innovative solution emerges from the Internet of Things (IoT), which enables the Water Quality Monitoring System (WQMAS) to transform traditional water resource monitoring practices. Through advanced sensor technologies, this system obtains real-time critical measurements including ambient temperature (25°C–30°C), water temperature (25°C–30°C), turbidity, pH values, electrical conductivity (500–1000 µS/cm), and dissolved oxygen levels. The system automatically pushes data into an easy-to-use IoT dashboard that allows users to immediately understand and assess data for smart and knowledgeable choices. The system utilizes Polyethylene Terephthalate Glycolmodified (PETG) material for durable 3D-printed enclosures that make it affordable and suitable for different fields due to its scalable characteristics and environmental resiliency. The automated system for water quality checks removes manual errors and performs fast and precise checks that manual operations cannot match. The technical capabilities of this solution become part of a sustainability showcase which enables communities to protect aquatic ecosystems while enhancing water resource optimization for creating a more environmentally friendly world. Within the water management industry, the Water Quality Monitoring System operates beyond its status as a tool to serve as a fundamental step towards sustainable development.